On Feeling Torn About One's Sexuality: The Effects of Explicit–Implicit Sexual Orientation Ambivalence. (September 2014) - Windsor-Shellard, Ben; Haddock, Geoffrey
Three studies offer novel evidence addressing the consequences of explicit–implicit sexual orientation (SO) ambivalence. In Study 1, self-identified straight females completed explicit and implicit measures of SO. The results revealed that participants with greater SO ambivalence took longer responding to explicit questions about their sexual preferences, an effect moderated by the direction of ambivalence. Study 2 replicated this effect using a different paradigm. Study 3 included self-identified straight and gay female and male participants; participants completed explicit and implicit measures of SO, plus measures of self-esteem and affect regarding their SO. Among straight participants, the response time results replicated the findings of Studies 1 and 2. Among gay participants, trends suggested that SO ambivalence influenced time spent deliberating on explicit questions relevant to sexuality, but in a different way. Furthermore, the amount and direction of SO ambivalence was related to self-esteem.